The age of revolutions in global context, c. 1760-1840 - Armitage, David, 1965-; Subrahmanyam, Sanjay (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2010)
"Distinguished historians provide uniquely broad coverage of the dynamics of global and regional change in the late eighteenth and nineteenth centuries. Sheds new light on the American, French and Haitian revolutions, alongside ground-breaking treatments of Africa's place in world history and Asia's age of revolutions"--Provided by publisher.
Introduction: the age of revolutions, c. 1760-1840: global causation, connection, and comparison / David Armitage and Sanjay Subrahmanyam -- Sparks from altar of '76: international repercussions and reconsiderations of the American Revolution / Gary B. Nash -- The French Revolution in global context / Lynn Hunt -- Revolutionary exiles: the American loyalist and French emigre diasporas / Maya Jasanoff -- Iberian passages: continuity and change in the South Atalntic / Jeremy Adelman -- The Caribbean in the age of revolution / David Geggus -- The dynamics of history in Africa and the Atlantic 'age of revolutions' / Joseph C. Miller -- Playing Muslim: Bonaparte's army of the Orient and Euro-Muslim creolization / Juan Cole -- Imperial revolutions and global repercussions: South Asia and the world, c. 1750-1850 / Robert Travers -- Revolutionary Europe and the destruction of Java's Old Order, 1808-1830 / Peter Carey -- Their own path to crisis? social change, state-building and the limits of Qing expansion, c. 1770-1840 / Kenneth Pomeranz -- The age of revolutions in global context: afterword / C.A. Bayly.
Includes bibliographical references and index.
Keywords: Revolutions -- History -- 18th century; Revolutions -- History -- 19th century; History, Modern -- 18th century; History, Modern -- 19th century